Planes de tesis y bibliografías excesivas - Ubertone, Fermín Pedro (2015)
This work seeks to open a dialogue with the Thesis Advisors and scholars responsible for evaluating academic research projects. The author criticizes the common practice of including an extensive bibliography in thesis plans. An over detailed bibliography is hardly credible in the first stage of the research as representing the actual knowledge of doctoral candidates. Rather, it appears to be an attempt to impress the evaluator.